리튬이온 배터리용 Cu-Steel 이종 레이저 용접부 응고균열에 미치는 Ni-P 도금의 영향 - 박재현; Jae-hyeon Park; 김명진; Myung-jin Kim; 강희신; Heeshin Kang; 천은준; Eun-joon Chun (대한금속·재료학회지, 62(7), 2024)
This study investigated the effect of a Ni-P coating layer on the solidification cracking behavior of Cu-mild steel dissimilar welds during the manufacturing of cylindrical Li-ion battery packs for electric vehicles. Four Cu plates were prepared and characterized: uncoated Cu and three levels (12, 50, and 100 μm) of Ni-P-coated Cu. The welding experiments used a single-mode fiber laser (2 kW) at extremely low heat input (1.82 J/mm) and high welding speed (1100 mm/s). Three laser beam patterns were used: linear, spiral, and wobble+spiral. Solidification cracking was detected for the Cu-Steel dissimilar welds for all the laser beam patterns on the uncoated Cu and the 50 and 100 μm Ni-P-coated Cu materials. Conversely, the dissimilar welds using 12 μm of Ni-P-coated Cu considerably suppressed solidification cracking behavior. Similarly, the welds with suppressed solidification cracking (using 12 μm of Ni-P-coated Cu) exhibited superior mechanical properties under the laser beam pattern. The weakest mechanical properties were confirmed for the welds using 100 μm of Ni-P-coated Cu. The solidification cracking and mechanical properties were highly dependent on the weld solidification of Ni and P. The suppression of solidification cracking in the welds using 12 μm of Ni-P coated Cu was attributed to the reduction in the weld mushy zone temperature range, due to the mixing of Ni, which reduced the solidification segregation of Cu. In contrast, the severe solidification cracking for the welds using 50 and 100 μm of Ni-P-coated Cu was estimated to result from the increased amount of incorporated P, which expands the weld mushy zone range.